Transient swelling of the Schneiderian membrane after transversal sinus augmentation: a pilot study. Issue 1 (29th October 2012) - Quirynen, Marc; Lefever, David; Hellings, Peter; Jacobs, Reinhilde
Abstract Objective The predictability and simplicity of the Summers' technique for sinus floor elevation encouraged many clinicians to consider this new approach. The impact of such intervention on the sinus mucosa has, however, not been explored extensively. This pilot study followed the response of the Schneiderian membrane, longitudinally, via cone‐beam CT images. Material and methods Ten consecutive patients (five women, mean age 58.7 years) referred for implant therapy in the posterior part of the maxilla, in combination with a trans‐alveolar sinus floor elevation (13 sinuses involved), were enrolled. CBCT images were taken prior to and at 1 week and 1 month after surgery. The changes in thickness of the Schneiderian membrane were scored at nine standardized points per sinus using reformatted cross‐sectional images. Results One week after sinus floor elevation, the Schneiderian membrane showed a significant swelling of 9.2 mm in the middle (SD 0.3; P < 0.005), 7.2 mm medially (SD 2.5; P < 0.005) and 3.9 mm laterally (SD 0, 3; P < 0.05), respectively, resulting in an overall mean of 6.7 mm (SD 2.6), which fully disappeared 3 weeks later. This swelling involved the entire floor of the sinus and not only the augmented area. Conclusions Within the limitations of this pilot study, one can conclude that the Schneiderian membrane responds with a significant "transient" swelling (5–10× its size) during the first weeks of healing.